FREEZE-DRYING KINETICS FOR DIFFERENT TYPES OF FOOD PRODUCTS - GHIRIŞAN (MICLĂUȘ), Adina (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This study presents the experimental data and the analysis of freeze-drying kinetics of three types of frozen food products: leaves of spinach and watercress, yeast suspension and pre-boiled wet rice. The effective diffusion coefficients for each product during dehydration are determined by applying the mass transfer model described by the Fick’s second law. The drying rates are obtained as a function of moisture content, and show specific curves of falling rate period.